Monitoring the state of health of first-year female students of NUPh in the 2018-2021 academic years - Anastasiia Nevelyka; Vasyl Sutula; Larysa Karabut; Olga Sutula; Alragad Raid (Фізична реабілітація та рекреаційно-оздоровчі технології, 2023)
The purpose of this research is to compare and determine the level of health of first-year female students of NUPh in the 2018-2021 academic years.